Where's the Geography department? The changing administrative place of Geography in UK higher education. Issue 1 (22nd January 2015) - Hall, Tim; Toms, Phil; McGuinness, Mark; Parker, Charlotte; Roberts, Neil
<x xml:space="preserve">Abstract</x> This paper considers recent patterns of departmental change in the management of Geography in UK universities. It notes the increasingly multidisciplinary management of Geography since the mid‐1990s. Various measures of this trend are explored and discussed. The paper also considers the problematic accommodation of Geography within the faculty structures of institutions. These findings speak of a problematic identity for the discipline within this institutional context. The paper goes on to consider some of the impacts of these trends for the practice of Geography in UK higher education.